Theology of the New Testament - Bultmann, Rudolf (London SCM Press, 1952)
The message of Jesus, the 'kerygma' of the early church and the theology of Paul.
Keywords: Bible. -- New Testament -- Theology. Bible. -- New Testament. Theology